Exogenous fibroblast growth factor 9 attenuates cartilage degradation and aggravates osteophyte formation in post-traumatic osteoarthritis. Issue 12 (December 2016) - Zhou, S.; Wang, Z.; Tang, J.; Li, W.; Huang, J.; Xu, W.; Luo, F.; Xu, M.; Wang, J.; Wen, X.; Chen, L.; Chen, H.; et al.
Summary: Objective: The aim of the present study is to investigate the effects of exogenous fibroblast growth factor (FGF)9 on the progression of post-traumatic osteoarthritis (OA). Design: The expression of FGF9 in articular cartilage with OA is detected by immunohistochemistry (IHC). The effects of intra-articular exogenous FGF9 injection on post-traumatic OA induced by the destabilization of the medial meniscus (DMM) surgery are evaluated. Cartilage changes and osteophyte formation in knee joints are investigated by histological analysis. Changes in subchondral bone are evaluated by microcomputed tomography (micro-CT). The effect of exogenous FGF9 on an interleukin-1β (IL-1β)-induced ex vivo OA model of human articular cartilage tissues is also evaluated. Results: FGF9 expression was down-regulated in articular chondrocytes of OA but ectopically induced at sites of osteophyte formation. Intra-articular injection of exogenous FGF9 attenuated articular cartilage degradation in mice after DMM surgery. Exogenous FGF9 suppressed collagen X and MMP13 expressions in OA cartilage, while promoted collagen II expression. Similar results were observed in IL-1β-induced ex vivo OA model. Intra-articular injection of FGF9 had no significant effect on the subchondral bone of knee joints after DMM surgery, but aggravated osteophyte formation. The expressions of SOX9 and collagen II, and cell proliferation were up-regulated at sites of initial osteophyte formation in mice with exogenous FGF9 treatment. Conclusions: Intra-articular injection of exogenous FGF9 delays articular cartilage degradation in post-traumatic OA, while aggravates osteophyte formation.